Echeandia cholulensis (Asparagaceae), a new species from central Mexico - Rodríguez, Aarón; Ortiz Brunel, Juan Pablo (Instituto de Ecología, A.C., 2021)
Background and Aims: The genus Echeandia (Asparagaceae) characterizes the Mexican geophyte flora. The group is exclusive of the Americas and includes 85 species. In Mexico, there are 74 species, of which 63 are endemic; however, the species richness is concentrated in the Mexican Transition Zone, including the Transmexican Volcanic Belt (TMVB). Here, we name and describe a new species of Echeandia found along the TMVB in the states of Puebla and Tlaxcala.Methods: Field work and herbarium revision led us to discover a new species of Echeandia. The morphological description and illustration were based on eight voucher specimens plus living plants from two populations. Moreover, we compared the morphology of the new taxon with that of E. michoacensis and E. robusta. Lastly, we assessed its conservation status by calculating its extent of occurrence (EOO) and its area of occupancy (AOO), using the GeoCAT tool and based on the IUCN Red List categories and criteria.Key results: Echeandia cholulensis is a new species from Mexico. The new taxon includes robust plants characterized by root-thickenings distant from the corm; lanceolate, undulate, and glaucous leaves; ascending flowers with white tepals; clavate and muricate filaments, and free anthers with longitudinal dehiscence. Until now, it is known from three populations in central Mexico in the states of Puebla and Tlaxcala.Conclusions: Along the TMVB, volcanism has created topographic and climatic variation favoring speciation and persistence. The discovery and morphological description of Echeandia cholulensis exemplifies this observation. Furthermore, botanical exploration and herbaria revisions might discover new species that would increase the great plant diversity of the TMVB.